Young’s modulus estimation techniques for the randomly oriented natural fiber reinforced composites: Finite element analysis and analytical models - Mustafa Bakkal; Mehmet Safa Bodur (Pamukkale University Journal of Engineering Sciences, 2019)
In the study, elastic modulus estimation methods of natural fiber reinforced composites considered as alternatives to synthetic fiber reinforced composites have been investigated. Finite element analysis (FEA) and some mathematical models which are used for synthetic fiber reinforced composites were preferred. During the study, randomly oriented cotton fiber reinforced composites at different fiber ratio by volume were investigated and the tensile test results were found experimentally. Experimental data were compared with data obtained using finite element method and current analytical models. Particularly in low fiber reinforced composite samples, the data obtained from the analytical models approximated between 2-4% of the experimental data. On the other hand, in the analysis by the finite element method, it is observed that the difference with the experimental results is opened as the high deformations are occurred. The most suitable analytical models have been found in the study and have been proposed for such composites. Moreover, the behavior of composites can be simulated by finite element methods and closed results (17-23%) are revealed in this respect.